(untitled) (Web of Teachers: Inderscience Research, 2025)
The purpose of this work is to acquaint students with vocal styles and various genres, in particular, to study the features of vocal expressiveness in folk songs, classical and modern music. styles in folk songs, classical music and modern genres, as well as their influence on musical development. This theme plays an important role in the development of students’ musical skills and the expansion of their musical and creative thinking. The article discusses various vocal styles, methods of their performance and how they affect students, contributing to the effectiveness of music education.